Vascular Cognitive Impairment in a Memory Clinic Population: Rationale and Design of the “Utrecht-Amsterdam Clinical Features and Prognosis in Vascular Cognitive Impairment” (TRACE-VCI) Study - Boomsma, Jooske Marije Funke (JMIR Res Protoc, 2017)
BACKGROUND: Vascular Cognitive Impairment (VCI) refers to cognitive dysfunction due to vascular brain injury, as a single cause or in combination with other, often neurodegenerative, etiologies. VCI is a broad construct that captures a heterogeneous patient population both in terms of cognitive and noncognitive symptoms and in terms of etiology and prognosis. This provides a challenge when applying this construct in clinical practice. OBJECTIVE: This paper presents the rationale and design of the TRACE-VCI study, which investigates the clinical features and prognosis of VCI in a memory clinic setting. METHODS: The TRACE-VCI project is an observational, prospective cohort study of 861 consecutive memory clinic patients with possible VCI. Between 2009 and 2013, patients were recruited through the Amsterdam Dementia Cohort of the VU University Medical Centre (VUMC) (N=665) and the outpatient memory clinic and VCI cohort of the University Medical Centre Utrecht (UMCU) (N=196). We included all patients attending the clinics with magnetic resonance imaging (MRI) evidence of vascular brain injury. Patients with a primary etiology other than vascular brain injury or neurodegeneration were excluded. Patients underwent an extensive 1-day memory clinic evaluation including an interview, physical and neurological examination, assessment of biomarkers (including those for Alzheimer-type pathologies), extensive neuropsychological testing, and an MRI scan of the brain. For prognostic analyses, the composite primary outcome measure was defined as accelerated cognitive decline (change of clinical dementia rating ≥1 or institutionalization) or (recurrent) major vascular events or death over the course of 2 years. RESULTS: The mean age at baseline was 67.7 (SD 8.5) years and 46.3% of patients (399/861) were female. At baseline, the median Clinical Dementia Rating was 0.5 (interquartile range [IQR] 0.5-1.0) and the median Mini-Mental State Examination score was 25 (IQR 22-28). The clinical diagnosis at baseline was dementia in 52.4% of patients (451/861), mild cognitive impairment in 24.6% (212/861), and no objective cognitive impairment in the remaining 23.0% (198/861). CONCLUSIONS: The TRACE-VCI study represents a large cohort of well-characterized patients with VCI in a memory clinic setting. Data processing and collection for follow-up are currently being completed. The TRACE-VCI study will provide insight into the clinical features of memory clinic patients that meet VCI criteria and establish key prognostic factors for further cognitive decline and (recurrent) major vascular events.